The role of perceived influence, brand engagement in self concept and expected value brand towards intention to purchase recommended brand on instagram content @jogjafoodhunter - Nanda Pradwiningtyas; Anas Hidayat (Institute of Computer Science (IOCS), 2022)
Marketing activities are essential to a business, including Instagram content such as @jogjafoodhunter. This study aims to analyze the role of perceived influence, brand engagement in self-concept, and brand expected value towards the intention to purchase recommended brands on Instagram content @jogjafoodhunter. Quantitative research design with the SmartPLS approach Active followers on the Jogja Food Hunter Instagram account was used in this study, and a sample of 300 people was taken by purposive sampling. The research instrument, in the form of a questionnaire, has been tested for validity and reliability—statistical data analysis with a confidence level of 95% (p<0.05). The results showed that various factors influence consumers' intentions in seeing, reviewing, buying, using, and recommending a product based on promoting influencers. In our findings, @jogjafoodhunter's content is influenced by brand expected value, intention to buy suggested brands, perceived influence, brand engagement in self-concept, and intention to purchase. All variables have a significant positive effect with a p- value of 0.000 (p<0.05). The better the marketing of content food products, specifically on Instagram @jogjafoodhunter, the higher the interest and purchasing power of consumers in the recommended products.